Ketogenic Diets and Hepatocellular Carcinoma - Lan, Yan; Jin, Chaonan; Kumar, Pavitra; Yu, Xia; Lenahan, Cameron; Sheng, Jifang (Frontiers in Oncology, 2022)
The ketogenic diet (KD) is a low-carbohydrate, high-fat diet regarded as a potential intervention for cancers owing to its effects on tumor metabolism and behavior. Hepatocellular carcinoma (HCC) is the most prevalent type of liver cancer, and its management is worth investigating because of the high fatality rate. Additionally, as the liver is the glucose and lipid metabolism center where ketone bodies are produced, the application of KD to combat HCC is promising. Prior studies have reported that KD could reduce the energy supply and affect the proliferation and differentiation of cancer cells by lowering the blood glucose and insulin levels. Furthermore, KD can increase the expression of hydroxymethylglutaryl-CoA synthase 2 (HMGCS2) in hepatocytes and regulate lipid metabolism to inhibit the progression of HCC. In addition, β-hydroxybutyrate can induce histone hyperacetylation and reduce the expression of inflammatory factors to alleviate damage to hepatocytes. However, there are few relevant studies at present, and the specific effects and safety of KD on HCC warrant further research. Optimizing the composition of KD and combining it with other therapies to enhance its anti-cancer effects warrant further exploration.